The dynamical organization of the core pluripotency transcription factors responds to differentiation cues in early S-phase - Oses, Camila; Francia, Marcos Gabriel; Verneri, Paula; Vazquez Echegaray, Camila; Guberman, Alejandra Sonia; Levi, Valeria (Frontiers in Cell and Developmental Biology, 2023)
DNA replication in stem cells is a major challenge for pluripotency preservation and cell fate decisions. This process involves massive changes in the chromatin architecture and the reorganization of many transcription-related molecules in different spatial and temporal scales. Pluripotency is controlled by the master transcription factors (TFs) OCT4, SOX2 and NANOG that partition into condensates in the nucleus of embryonic stem cells. These condensates are proposed to play relevant roles in the regulation of gene expression and the maintenance of pluripotency. Here, we asked whether the dynamical distribution of the pluripotency TFs changes during the cell cycle, particularly during DNA replication. Since the S phase is considered to be a window of opportunity for cell fate decisions, we explored if differentiation cues in G1 phase trigger changes in the distribution of these TFs during the subsequent S phase. Our results show a spatial redistribution of TFs condensates during DNA replication which was not directly related to chromatin compaction. Additionally, fluorescence fluctuation spectroscopy revealed TF-specific, subtle changes in the landscape of TF-chromatin interactions, consistent with their particularities as key players of the pluripotency network. Moreover, we found that differentiation stimuli in the preceding G1 phase triggered a relatively fast and massive reorganization of pluripotency TFs in early-S phase. Particularly, OCT4 and SOX2 condensates dissolved whereas the lifetimes of TF-chromatin interactions increased suggesting that the reorganization of condensates is accompanied with a change in the landscape of TF-chromatin interactions. Notably, NANOG showed impaired interactions with chromatin in stimulated early-S cells in line with its role as naïve pluripotency TF. Together, these findings provide new insights into the regulation of the core pluripotency TFs during DNA replication of embryonic stem cells and highlight their different roles at early differentiation stages.